Perbandingan Pembelajaran Daring dan Luring Menggunakan Model PBL terhadap Pemahaman Siswa pada Materi Sistem Reproduksi Manusia - Purwati Purwati; Abd Muis; Dahniar Dahniar (Celebes Science Education, 2024)
This study aims to determine the comparison of the level of students' understanding of the human reproductive system material using the Problem Based Learning model which is carried out offline and online on class IX-A students of SMPN 2 Martapura. The type of this research is classroom action research with the research subjects being class IX-A students in the odd semester of 2021/2022 totaling 16 people. Based on the average pre-test score, it was 46.88 and the post-test was 81.75 for offline, while for online, the average pre-test was 64.25 and the post-test was 79.69. The results obtained showed an increase of 34.87 in offline learning and 15.44 in online learning. The completeness of learning outcomes classically in offline learning was 87.5% and in online learning 81.25%. Based on the results of this study, it can be concluded that offline learning improves students' understanding more than online learning.